POLAROGRAFI DENYUT UNTUK PENENTUAN KADAR EMAS DALAM LARUTAN CAMPURAN DENGAN TEMBAGA DAN PERAK TANPA PROSES PEMISAHAN - Soefjan Tsauri (Research Center for Chemistry - LIPI, 1991)
Pulse Polarographic determination of gold (- 2 ppm) in a solution mixture with the presence of silver and copper ion without separation has been examined. Utilizing the suitable condition, polarographic peaks of gold, silver and copper were separated and thus could make the determination of gold possible in a solution with silver and copper ions. From the investigations carried out, several conclusions were derived i.e. : 1. A system of KOH 1,5M, KN03 0,02 M and KCN 0,01M, which was then called the complexing and supporting electrolyte mixture or